Pengaruh Variasi Daya Bi-LED Projector dan Penggunaan Voltage Stabilizer terhadap Fluks Cahaya pada Sepeda Motor - Hafizh Ramadhani Zuhriansyah; Khambali Khambali; Yuniarto Agus Winoko; Purwoko Purwoko (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of variations in bi-LED projector power and the use of a voltage stabilizer on the luminous flux on a motorcycle. The luminous flux produced by a motorcycle lighting system plays a very important role in improving rider visibility and safety, especially at night. Therefore, this study uses a quantitative experimental method with a two-way factorial approach (Two-Way ANOVA) to test the effect of two main variables, namely the bi-LED projector power and the voltage stabilizer configuration. The power variables tested include three power levels, namely 35 W, 70 W, and 105 W, while the voltage stabilizer configuration includes three conditions, namely without a stabilizer, 14 V, and 14.5 V. Luminous flux measurements were carried out using a lux meter at a distance of five meters from the reflective surface, and the results were then combined into lumen units to facilitate comparison between power variations and stabilizers. The results showed that increasing the bi-LED projector power significantly increased the luminous flux produced. The 105 W power output produced the highest luminous flux, reaching 42,319 lumens when combined with a 14.5 V voltage stabilizer. This demonstrates that the combination of high power and proper voltage stabilizer use can improve the quality of motorcycle lighting. The very low P-value (0.000) and R² of 100% indicate that the predictive model used in this study is robust and reliable. Overall, this study emphasizes the importance of using a voltage stabilizer in motorcycle lighting systems. A voltage stabilizer is not only a complementary device but also a crucial component for improving visibility and driving safety, especially at night. Therefore, proper use of a stabilizer can improve lighting performance and provide significant safety benefits.